A review of phthalate pharmacokinetics in human and rat: what factors drive phthalate distribution and partitioning?. (3rd July 2019) - Domínguez-Romero, Elena; Scheringer, Martin
Abstract: Phthalates are a class of compounds that have been extensively used as plasticizers in different applications. Several phthalates have been recognized as substances of very high concern (SVHCs) in the EU, because of their toxicity for reproduction. However, high amounts of other phthalates are still produced and imported in the European Economic Area. In China and the US, recent studies show increasing concentrations of several phthalates in the air and in human urine, respectively. The understanding of phthalate absorption, distribution, metabolism, and elimination ('pharmacokinetics') in the organism is still limited. Specifically, phthalate partitioning among tissues is insufficiently understood. Here, we estimate partition coefficient (PC) values for different phthalates by using five algorithms and compare them to experimental ( in-vivo and in-vitro ) PC values. In addition, we review all pharmacokinetic steps for phthalates in human and rat, based on data from 133 peer-reviewed publications. We analyze the factors that determine phthalate partitioning and pharmacokinetics. Four processes are particularly relevant to phthalate distribution: protein binding, ionization, passive partitioning, and metabolism in different tissues. The interplay of these processes needs to be better represented in methods for determining the PC values of phthalates. The hydrophobicity of phthalates affects all pharmacokinetic steps. The exposure route has an influence on specific steps of phthalate pharmacokinetics but generally does not affect the pattern of metabolites in urine. The age of the organism has an influence on phthalate metabolism. More studies on the protein-bound fraction of phthalates in plasma and pharmacokinetic studies following inhalation and dermal exposure are desirable.